Cultural Untranslatability in Tamil–English Translation: Approaches of Newmark and Mona Baker in Rendering "வீரமுனைப் பதியின் கூத்துக்கலைகள் - ஒர் ஆய்வுப் பார்வை" - Rameesa, A.; Kannathas, K. (Faculty of Arts University of Jaffna, Sri Lanka, 2025)
This study examines the challenges of translating culturally embedded words and expressions from Tamil into English, with a particular focus on the traditional Tamil dramatic art form, Koothu. Since many terms associated with this genre lack direct English equivalents, translators often face difficulties in conveying their full meaning. The aim of this research is to explore how cultural untranslatability can be addressed by applying the procedures suggested by Peter Newmark and Mona Baker, while the objectives are to identify key categories of cultural challenges, analyze the strategies used in translation, and assess the effectiveness of these procedures in bridging cultural gaps. The research adopts a qualitative approach, concentrating on the transfer of cultural meaning in translation. The primary data consists of the Tamil source book “வீரமுனைப் பதியின் கூத்துக்கலைகள் ஒர் ஆய்வுப் பார்வை” and its English translation, The Traditional Tamil Dramatic Art of Koothu in Veeramunai. The theoretical framework is based on two major works in translation studies: Peter Newmark’s A Textbook of Translation (1988) and Mona Baker’s In Other Words: A Coursebook on Translation (1992). Secondary data is drawn from scholarly books, journal articles, and research papers on cultural untranslatability and translation procedures. The study identifies five main categories of cultural challenges: socio-cultural terms, material culture, ecological references, vocabulary related to aesthetic art form, and compact words carrying deeper cultural meanings. To resolve these, strategies such as couplets, descriptive equivalents, paraphrasing, synonyms, transference, loan words, compensation, generalization, and notes are applied. The findings demonstrate that Newmark’s and Baker’s procedures provide effective solutions for overcoming cultural untranslatability, but they require careful adaptation to suit specific cultural contexts. This research contributes to Translation Studies by expanding knowledge on the translation of culturally rich and specialized art forms, specifically the genre of Koothu, which has been relatively underexplored in academic discourse. It also offers practical guidance for translators working with similar culturally bound texts.
Keywords: Cultural untranslatability; Mona Baker; Peter Newmark; Tamil dramatic art (Koothu); Translation procedures